Síntese de novos complexos de platina(II) de interesse biológico. Um novo complexo dinuclear de platina(II) com 5-fluorouracil - Cavicchioli, M. [UNESP]; Payolla, F. B.; Massabni, A. C. [UNESP] (My University, 2015)
Phasellus Many strategies have been used for the treatment of cancer and, following the success of cisplatin and carboplatin, metal complexes have been excelled and showed efficiency on the treatment of many types of cancer. The use of ligands that already have antitumor activity allows an increase on the drugs efficiency. In this work, synthesis of obtained a binuclear compound of platinum and 5-fluorouracil is described. The compound was characterized by elemental analysis and the results show a molar ratio of 2:1 (M:L). The IR spectra shows the complexation of the ligands to the metal by the N atoms of the ligand. On the free ligand spectrum, it is possible to note the N-H bond stretch at 3160 cm-1. The displacements of the frequencies of the C=O groups on the region of 1720cm-1 and 1652cm-1 to 1575cm-1 and 1504cm-1, respectively, occur because of the coordination of the metal to the N neighbour atoms of the ligand.
Synthesis of novel platinum(II) complexes of biological interest. A novel dinuclear platinum(II) complex with 5-fluorouracil
Keywords: Antitumoral; Complex platinum(II); Fluorouracil